Developing project-based learning tools for light vehicle engine maintenance subjects at vocational high school - Muslim Muslim; Ambiyar Ambiyar; Dedi Setiawan; Rido Putra (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2020)
This study aims to develop learning tools for project-based light vehicle engine maintenance and describe the teacher's response to the application of project-based learning tools in light vehicle engine maintenance subjects. This research is a research and development (R&D) model with ADDIE. The ADDIE development model consists of analysis, design, development, implementation, and evaluation. The results showed that the product developed was valid in terms of validity, very practical in terms of practicality, and very high in the aspect of effectiveness. Based on the aspects of validity, it can be specified that the syllabus gets a percentage score of 90.25%, 88.78% learning implementation plan, 86.56% module, 88.93% job sheet, 87.5% achievement test instrument, and project test instrument 87.08%. Based on aspects of practicality assessed from the teacher's response, it can be specified that the syllabus gets a percentage score of 88.67%, 86.88% learning implementation plan, 88.75% module, 88.77% job sheet, 85.42% test instrument for learning outcomes, and 83.33% project test instruments. Overall, teachers find it helpful to develop project-based learning tools. Based on the effectiveness, the results of students' knowledge tests with the percentage of mastery learning in the knowledge area amounted to 86.67%, and the skill area amounted to 86.67% with very high criteria. Researchers can conclude that project-based learning tools on light vehicle maintenance subjects are in accordance with valid, practical, and effective criteria.